(untitled) (Indian Journal of Arid Horticulture, 2025)
Ker (Capparis deciduas L.) of family Capparidaceae is a multipurpose tree which is distributed throughout the arid regions of India and other countries. The plant is xerophytic in nature and is highly tolerant to drought conditions for long period. The plant is used traditionally as anti-inflammatory, laxative, anti-diabetic, anthelmintic, antibacterial, astringent, digestive, diaphoretic and anodyne. Ker fruits are used to make delicious pickle. The major constraint in development of orchards of this species is lack of true to type planting material. This is on account of fact that systematic vegetative propagation technique is yet to be standardized. Presence of inhibitors has been shown in cuttings of ker (Bhargava et al., 2000). Ker is commonly propagated through seeds. However, the uniformity of seed germination and subsequent seedling growth further aggravate the problem. Accordingly, in the present study, an attempt was made to study the effect of different concentrations of GA, KNO, and Salicylic acid on germination of ker seeds and seedling growth.